Thermal conductivity enhancement of phase change material with charged nanoparticle: A molecular dynamics simulation. (1st March 2022) - Zhao, C.Y.; Tao, Y.B.; Yu, Y.S.
Abstract: The present work investigates the effects of charged nanoparticles on thermal properties of phase change material (PCM). Nanoparticles (CuO) with different electrical charges were dispersed into paraffin (octadecane) to prepare nanocomposite phase change material (NPCM). Molecular dynamics method was used to study the thermal conductivity of NPCM and reveal the effect of the charged nanoparticle. The results show that the thermal conductivity of NPCM is promoted with increasing nanoparticle charges. Coulomb energy is nonlinearly increased with the increasing charge. Furthermore, the local density of atoms is also affected by the charged nanoparticle. The peak value of local density increases with increasing nanoparticle charges. Phonon density of state (PDOS) is calculated to study the phonon transport in NPCM. Phonon scattering is weakened around the nanoparticle due to the existence of nanolayer. Moreover, the thickness of nanolayer is increased with the increasing charge, resulting in weaker phonon scattering and contributing to more thermal conductivity enhancement of NPCM. It can be a good way to control the thermal properties of NPCM by adjusting the nanoparticle charge. Highlights: Charged nanoparticles enhance the thermal conductivity of NPCM. Local density of atoms shows peaks and indicates nanolayer. Coulomb energy is nonlinearly increased with increasing nanoparticle charges. The thickness of nanolayer increases with increasing nanoparticle charges.